Machining performance of reinforced alumina insert in end milling of AISI 1018 steel - H.M. Nor Hakim; R.M. Ikhwan Zaini; Z.A Ahmad; Abdullah Mohd Mustafa Al Bakri; Ahmad Bakir Azman; Mazlan Mohamed (Trans-Tech Publication, 2013)
The main goal of this work is to investigate the performance of zirconia toughened alumina (ZTA) and ZTA reinforced with magnesium oxide (MgO) used as cutting insert in end milling of AISI 1018 steel with hardness of 27 HRC. Performances of the cutting insert were compared according to tool life and surface finish of workpiece. Insert flank wear that indicates tool life was studied carefully using Optical 3D Surface Metrology while surface roughness values were evaluated using Surftest Sufrcom 130A. The cutting inserts failed to exhibit good performance in end milling operation. However, wear condition and magnitude of the ZTA reinforced with MgO insert was slightly better than ZTA insert. Addition of MgO may increase wear resistance.